2008
DOI: 10.1111/j.1365-2044.2008.05539.x
|View full text |Cite
|
Sign up to set email alerts
|

A case series of the use of the ProSeal laryngeal mask airway in emergency lower abdominal surgery

Abstract: SummaryThe ProSeal laryngeal mask airway (PLMA) has been used routinely for anaesthesia and for difficult airway management including airway rescue in non-fasted patients. Compared with the classic laryngeal mask airway the PLMA increases protection against gastric inflation and pulmonary aspiration, by separating the respiratory and gastro-intestinal tracts. The PLMA has potential advantages over use of the tracheal tube including smoother recovery, reduced pharyngolaryngeal morbidity and even reduced postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…However, tracheal intubation has been recently challenged by a case series involving 102 patients for emergency appendicectomy who each received a ProSeal laryngeal mask airway without complications [10].…”
Section: Resultsmentioning
confidence: 99%
“…However, tracheal intubation has been recently challenged by a case series involving 102 patients for emergency appendicectomy who each received a ProSeal laryngeal mask airway without complications [10].…”
Section: Resultsmentioning
confidence: 99%
“…2 also hints at the answer to another question posed earlier: how to interpret trials in which there are no failures. There are many such 'zero failure' trials reported in the anaesthetic literature [7,8,15]. This question has been discussed extensively before [1,10,11].…”
Section: Variation Of Confidence Intervals With Prevailing Failure Ratementioning
confidence: 99%
“…Fabregat-Lopez ve ark. 7 proseal LMA kullanımında rokuronyumu güvenle kullanmışlardır. Hızlı ve güvenli havayolu sağlaması yanında gastrik boşaltma tüpünün olması mide drenajı sağlayarak aspirasyon riskini ortadan kaldırır.…”
Section: Discussionunclassified